Perbandingan Metode Ekstraksi terhadap Kadar Flavonoid Total Ekstrak Etanol Daun Kersen (Muntingia Calabura L.) - Alfiraza, Ery Nourika; Nurhidayati, Lailiana Garna; Fahamsya, Arifina; Wahyuningtias, Arum (Journal of Pharmaceutical and Health Research, 2024)
Flavonoid compounds, triterpenes, tannins, polyphenols, and saponins can be found in cherry leaves (Muntingia calabura L.). Flavonoids are proven to be able to reduce free radicals, and thus can act as an antioxidant. The use of extraction methods can affect the content of flavonoid compounds contained in the extract . Thus, to extract flavonoids from plant leaves, it is necessary to optimize the right extraction method. Objective of this study was to compare the effect of using three different extraction methods, namely maceration, reflux, and sonication, on the total flavonoid content of cherry leaf ethanol extract. Cherry leaves were extracted with ethanol (1:10), using three different extraction methods, namely maceration, reflux, and sonication. The viscous extract obtained was then measured for total flavonoid content using UV-VIS spectrophotometry at 431 nm, using a standard solution of quercetin as a comparison. Total flavonoid content of ethanol extract of cherry leaf extracted by maceration, reflux, and sonication method respectively were 73.98 ± 0.06 mgQE/g; 60.55 ± 0.05 mgQE/g; and 92.53 ± 0.12 mgQE/g. Conclusion of this study was The extraction process influences the overall flavonoid concentration of cherry leaf ethanol extract.